Balancing risk reduction and benefits from trade in setting standards: food safety in food security and food trade - Wilson, John; Otsuki, Tsunehiro (International Food Policy Research Institute, 2003)
Growing concern over health risks associated with food products has prompted close examination of sanitary and phytosanitary (SPS) standards in industrialized countries. Standards are employed to protect human health from toxic additives, contaminants, toxins, or disease-causing organisms in foods and beverages, as well as to protect animal and plant health from diseases. Measures used to protect health include outright bans, standards that dictate the conditions under which products must be produced and/or characteristics of the end products, and labelling and other information requirements....Both anecdotal and case-study evidence indicates that the cost of food-safety regulations indeed can be significant. This is especially true for developing countries attempting to penetrate developed-country agricultural markets. -- from Text